FULL SCREEN AHEAD. - Davis, Hazel (Strad, 2011)
The article offers information on the use of technology by classical musicians. It states that Nicholas Kitchen, a violinist of the Borromeo String Quartet uses technology in classical music wherein their use laptops for both performing and rehearsing. It also mentions that the Borromeos use Apple MacBook Pro computer, wherein each sits on a laptop stand that is connected to a Footime page-turner made by Bili Inc. through USB that allows the musicians to turn pages by pressing foot buttons.